Women and resistance in the early Rastafari movement - Dunkley, Daive A. (Louisiana State University Press, 2021)
"Women and Resistance in the Early Rastafari Movement is a pioneering study of women's resistance in the emergent Rastafari movement in colonial Jamaica. The movement was established in Jamaica in 1932 as a challenge to British colonialism and racism, and was roundly denounced by the government and many Jamaicans. At the same time, the Rastafari movement remained heavily patriarchal, so that women involved had to contend not only with the various attempts made by the government to suppress the movement, but also with oppression and silencing from among their own ranks. Unfortunately, the absence of research on these women has helped to perpetuate the myth that Rastafari women were widely silent and subordinate to the male leaders. Women and Resistance in the Early Rastafari Movement examines the lives and experiences of a group of Rastafari women between the movement's inception in 1932 and Jamaica's independence from Britain in 1962. Countering many years of scholarship that privilege the stories of Rastafari men, this study uncovers some of the early Rastafari women's sense of agency and resistance against both male domination and societal opposition to their Rastafari identity. Though the primary sources for a study of early Rastafari women are scarce, Daive Dunkley brings together materials from the government archives, newspapers, and oral sources to reconstruct various aspects of the lives of these women. Dunkley argues that the woman in this study made themselves critical to the early growth and resistance ethos of Rastafari, ensuring that it challenged discrimination and suppression based on class and gender, as well as religion and race. Early women promoted the transition of the movement into the creation of interracial alliances, which in turn aided the movement's development into a global phenomenon"--